Correlation between compression and flexure strength of concrete, applying accelerating additive at ages from 3 to 180 days - Peralta Quiroz, Hansel Leonardo; Mosqueira Ramírez, Hermes Roberto (LACCEI, 2025)
Concrete continues to be the most used material in civil constructions; in certain locations there are some conditions that make the use of chemical additives essential, such as accelerating additives; This additive is widely used, but its influence on resistance at ages after 28 days is unknown. Likewise, it is known that flexural resistance is a property directly related to compression resistance; However, it is unknown what correlation exists between these for a type of concrete and at different ages. This research presents the results of the study carried out to determine the correlation between the compressive and flexural strength of concrete f'c 27,46 MPa, applying accelerator additive, in the city of Cajamarca. The evaluation was carried out by calculating the correlation between the results of flexural and compression resistance of standard concrete, concrete with 2,50% accelerating additive and concrete with 4,00% accelerating additive, at 6 ages of concrete in the hardened state (3, 7, 28, 60, 90 and 180 days). To determine the correlation, 30 standard cylindrical specimens and 18 beams were made for each treatment, tested in compression and flexion at ages of 3, 7, 28, 60, 90 and 180 days, with a total of 144 specimens. From the results, the correlation was calculated, concluding that there is a correlation between both resistances, with the resistances being exponentially greater over time.